1978
DOI: 10.1055/s-0028-1104774
|View full text |Cite
|
Sign up to set email alerts
|

Wirkung von Molsidomin auf die Hämodynamik in Ruhe und unter Belastung bei Patienten mit koronarer Herzkrankheit

Abstract: In ten patients with coronary heart disease molsidomine achieved a clear-cut decrease in pre- and after-load of the heart at rest. Due to decreased venous return at rest there was a fall in stroke volume resulting in a fall of systolic and diastolic aortic pressure. But at the same level of standardised exercise, systolic and diastolic arterial pressure and cardiac output were similar with or without molsidomine. Without changing after-load, there was a fall in pulmonary artery mean pressure (P less than 0.005… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1981
1981
1989
1989

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Animal experiments (8,11,15,29) and clinical studies (5,19,20,(25)(26)(27) demonstrated that the reduction of intramyocardial wall tension due to lowered preload is the main therapeutic principle of the drug. Because of the documented long duration of its antianginal and venodilating action molsidomine may be a promising candidate for pharmacological prophylaxis of anginal attacks.…”
Section: Discussionmentioning
confidence: 99%
“…Animal experiments (8,11,15,29) and clinical studies (5,19,20,(25)(26)(27) demonstrated that the reduction of intramyocardial wall tension due to lowered preload is the main therapeutic principle of the drug. Because of the documented long duration of its antianginal and venodilating action molsidomine may be a promising candidate for pharmacological prophylaxis of anginal attacks.…”
Section: Discussionmentioning
confidence: 99%
“…Molsidomine has been shown to be an effective agent in the treatment of angina pectoris (Blazek et a/., 1977;Jansen and Klepzig, 1978;Majid e(a/., 1980). In previous studies reduction of myocardial ischemia by treatment with molsidomine was demonstrated by clinical relief of symptoms and by electrocardiographic and hemodynamic response to exercise (Grewe and Stauch, 1977;Niehues et a/., 1978;Slany et a/., 1976). The basic mode of action is a reduction of left ventricular wall tension, primarily by the venodilator capacity of the drug (Majid et a/., 1980).…”
Section: Introductionmentioning
confidence: 94%
“…The basic mode of action is a reduction of left ventricular wall tension, primarily by the venodilator capacity of the drug (Majid et a/., 1980). Studies in animals Grund et a/., 1978; and in men (Majid et a/., 1980;Niehues et a/., 1978) have shown that the drug-induced hemodynamic changes are similar to those of nitrates, but therapeutic effectiveness seems to be longer lasting (Hashimoto et al, 1971;Takeshita et al, 1977). Although nitroglycerin and other nitrates have been extensively employed in the treatment of angina pec-W. Nechwatal el al.…”
Section: Introductionmentioning
confidence: 99%